Two new endemic Begonia species named after historical landmarks of Ilocos Sur, Philippines - Calaramo, Michael Agbayani; Rubite, Rosario Rivera; Lin, Che-Wei (Phytotaxa, 2023)
Two new species of Begonia endemic to the Philippines are described from the province of Ilocos Sur, Northwestern Luzon: Begonia tiradpassensis (B. sect. Baryandra) from Tirad Pass, and Begonia bessangpassensis (B. sect. Petermannia) from the subsummit of Bessang Pass Natural Monument/Landmark. Based on IUCN Red List list criteria, B. tiradpassensis & B. bessangpassensis are provisionally assessed to be threatened, as they are confined to small populations with anthropogenic disturbance surrounding their distribution area. The discovery of these species highlights the conservation importance of two historical landmarks, Tirad Pass and Bessang Pass, which have left an indelible mark on Philippine history.